Assessment of knowledge, attitudes, and professional behavior toward silver diamine fluoride among postgraduate pediatric dentistry students - Anju Vinod; N. Sunil Raj; Anitha Anand (Journal of Oral Research and Review)
Background and Objectives: Silver diamine fluoride (SDF) is a clear solution composed of ammonia, silver, and fluoride ions, used as an alternative treatment for early childhood caries. The study sought to assess the educational experiences, knowledge, attitudes, and professional behavior of postgraduate pediatric dentists regarding SDF, as well as to explore the connections among these factors. Methods: Postgraduate pediatric dental students (n = 200) participated in the survey. The SDF evaluation covered education, clinical knowledge, attitudes, and professional behavior, as well as parental acceptance. Results: Despite the limited scope of undergraduate education regarding SDF, the majority of the respondents knew about its uses and limitations. In spite of their high knowledge and positive attitude, the clinical use of SDF was found lacking. There was a positive correlation between the constructs, and the associations were statistically significant (P = 0.00). Interpretation and Conclusion: Even with the knowledge and positive attitude, clinical use seemed lacking. This can be overcome by increasing SDF education and encouraging postgraduates to incorporate the use of SDF into their routine practice. Moreover, clinicians must stress the advantages of SDF to parents and encourage them to look beyond the esthetic limitations.